Status of production, distribution and determinants of biomass briquette acceptability in kampala, uganda - Mugabi, P.; Kisakye, D.B. (Maderas. Ciencia y Tecnología, 2021)
Biomass briquettes have been identified as a plausible and close alternative to commonly used energy fuels such as charcoal and firewood whose prices are escalating due to the dwindling natural resource base. However, briquettes do not seem to be as popular as would be expected. This study assessed the production, distribution and acceptability of the briquettes in Kampala district. A total of 60 respondents, 50 of whom were briquette users and 10 briquette producers were sampled from five divisions of Kampala district to evaluate consumer acceptability, preference for briquette type and shape. Households and institutions were identified to be the major consumers of briquettes while community-based organizations were the major distributors of briquettes. The Chi square test of independence showed significant association between briquette acceptability and briquette attributes of substitutability and low cost (p<0.05). The Kruskal Wallis test showed that low income class people preferred non-carbonized briquettes. Gender, marital status and income level also cause variation in preference for spherical, stick and honey comb briquettes (p<0.05). The major challenges faced by briquette users in Kampala were; production of a lot of ash, frequent crushing and limited access of briquettes. The producers of briquettes were mainly challenged by regular machine breakdown, raw material scarcity and poor carbonizing units. It was concluded that briquettes have market and are generally accepted in Kampala. However, user preferences need to be taken into account by briquette produces, suitable cook stoves should be availed to users and there is need for standards to ensure quality of briquettes.